2022
DOI: 10.1080/19490976.2022.2138672
|View full text |Cite
|
Sign up to set email alerts
|

Artificial intelligence-based personalized diet: A pilot clinical study for irritable bowel syndrome

Abstract: We enrolled consecutive IBS-M patients (n = 25) according to Rome IV criteria. Fecal samples were obtained from all patients twice (pre-and post-intervention) and high-throughput 16S rRNA sequencing was performed. Six weeks of personalized nutrition diet (n = 14) for group 1 and a standard IBS diet (n = 11) for group 2 were followed. AI-based diet was designed based on optimizing a personalized nutritional strategy by an algorithm regarding individual gut microbiome features. The IBS-SSS evaluation for pre- an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 34 publications
0
16
0
Order By: Relevance
“…In addition to its application in digital images, AI holds great promise for the future in big data analysis in the medical field. With advancements in machine learning algorithms and the availability of large datasets, AI can help clinicians and researchers identify novel biomarkers, 63 understand disease mechanisms, 64 and develop personalized treatments 65 . Additionally, AI can facilitate the integration of multi‐omics data and improve the accuracy of diagnoses and prediction 66,67 .…”
Section: Current Challenges and Future Perspectivesmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to its application in digital images, AI holds great promise for the future in big data analysis in the medical field. With advancements in machine learning algorithms and the availability of large datasets, AI can help clinicians and researchers identify novel biomarkers, 63 understand disease mechanisms, 64 and develop personalized treatments 65 . Additionally, AI can facilitate the integration of multi‐omics data and improve the accuracy of diagnoses and prediction 66,67 .…”
Section: Current Challenges and Future Perspectivesmentioning
confidence: 99%
“…With advancements in machine learning algorithms and the availability of large datasets, AI can help clinicians and researchers identify novel biomarkers, 63 understand disease mechanisms, 64 and develop personalized treatments. 65 Additionally, AI can facilitate the integration of multi-omics data and improve the accuracy of diagnoses and prediction. 66,67 It could even be used to discover or identify new drugs.…”
Section: Current Challenges and Future Perspectivesmentioning
confidence: 99%
“…In contrast to conventional treatment, AI-assisted personalized therapy has improved bowel habits, abdominal pain relief, and quality of life. 123 Additionally, the efficacy of probiotic-based therapy can be increased with the help of multiple pharmaceutical excipients. For the first time, Mc Coubrey et al 124 applied the ML approach to report the impact of 111 pharmaceutical ingredients to enhance the proliferation of L. paracasei.…”
Section: Ai/ml Utilizes the Molecular Characteristics Of Bacteriamentioning
confidence: 99%
“…To enhance this purpose, an algorithm, i.e., XGBoost, has been used to determine the irritable bowel severity (IBS)-index score for personalized dietary modulation in inflammatory bowel disease (IBD) patients. In contrast to conventional treatment, AI-assisted personalized therapy has improved bowel habits, abdominal pain relief, and quality of life . Additionally, the efficacy of probiotic-based therapy can be increased with the help of multiple pharmaceutical excipients.…”
Section: Ai/ml-based Precision Probiotic Selection For Advanced Healt...mentioning
confidence: 99%
“…One effective dietary intervention for IBS is the low fermentable oligosaccharides, disaccharides, monosaccharides and polyols diet. 8 A very recent article by Karakan et al (2022) 9 reported an interesting study where they considered a total n = 25 baseline group of IBS patients, and the healthy controls (n = 34) were compared in terms of their microbiota compositions. Out of n = 25 patients, 6 weeks of a personalized nutrition diet (n = 14) for group 1 and a standard IBS diet (n = 11) for group 2 were followed and then compared.…”
mentioning
confidence: 99%